Biology, distribution and management of the globally invasive weed Solanum elaeagnifolium Cav (silverleaf nightshade): A global review of current and future management challenges. (9th October 2022) - Roberts, Jason; Florentine, Singarayer
Abstract: Solanum elaeagnifolium Cav (silverleaf nightshade) is a deep‐rooted, multi‐stemmed, perennial, herbaceous woody plant that has been observed to threaten agricultural and native biodiversity worldwide. It is widely agreed that without efficient integrated management, S. elaeagnifolium will continue to cause significant economic and environmental damage across multiple scales. It is estimated that the annual economic impact of S. elaeagnifolium in Australia exceeds AUD $62 million, with this figure likely to be much higher in other countries invaded by this plant. It can also tolerate a high level of abiotic stress and survive in a range of temperatures (below freezing point to 34°C) and areas with an average yearly rainfall between 250 and 600 mm. Its extensive deep taproot system is capable of regenerating asexually and with its many seed dispersal mechanisms; it can quickly spread and establish itself within a region. This makes containment and management of the species especially challenging. Previous management has largely been focused on biological control, competition, essential oils, grazing pressure, herbicide application and manual removal. Despite the large range of available management techniques, there has been little success in the long‐term control of S. elaeagnifolium, and only a handful of methods such as essential oils and herbicide application have shown reasonable success for controlling this weed. Therefore, this review aims to synthesise the identified and potentially useful approaches to control S. elaeagnifolium that have been recorded in the literature which deal with its biology, distribution and management. It also explores previous and current management techniques to ascertain the research gaps and knowledge required to assist in the effective and economically sustainable management of this invasive weed.